The Strategy of Developing Kreo Cave Tourism - Tutik, Tutik; Prajanti, Sucihatiningsih Dian Wisika; Kardoyo, Kardoyo (Journal of Economic Education, 2018)
The potential which is possessed by tourism object of Kreo Cave still needs to be developed again so that it becomes the major of tourism destination that is the most attractive in Semarang city. Therefore, it is needed the strategy of developing the tourism object that is really prepared carefully accompanied by a good handling by the manager of the Kreo Cave tourism object. The objectives of the research are (1) Assessing and analyzing tourist attraction strategies in the development of Kreo Cave Tourism Object in Semarang. (2) Reviewing and analyzing tourism facility strategies in the development of Kreo Cave Tourism Object in Semarang. (3) Reviewing and analyzing the accessibility strategies in developing Kreo Cave Tourism Object in Semarang. (4) Reviewing and analyzing the hospitality strategies in the development of Kreo Cave Tourism Object in Semarang. (5) Reviewing and analyzing the government support strategies in developing Kreo Cave Tourism Object in Semarang. (6) Reviewing and analyzing the tourism promotion strategies in the development of Kreo Cave Tourism Object in Semarang. The method of collecting data in this research was by using questionnaire and interview techniques. This type of the research was qualitative with SWOT analysis method. The result of descriptive qualitative shows the profile and condition of Kreo Cave Tourism Object, while the result of the calculation of SWOT analysis shows that Kreo Cave is in quadrant one, has the dominant strengths and opportunities that have the potential to be developed.